Fungal pneumonia manifesting as cavitary lesions in a critically ill elderly patient - Yang, Wei; Ma, Yixin; Wang, Jieyu; Li, Yun; Zhang, Yaxin; Zhang, Tong (The Journal of Infection in Developing Countries, 2019)
Elderly patients with fungal pneumonia experience higher mortality and are more likely to be misdiagnosed. The diagnosis and treatment of fungal pneumonia in elderly patients is challenging. We herein present a clinical case of pulmonary fungal infection (PFI) manifesting as cavitary lesions in an 85-year-old male with multiple organ failure. Broad-spectrum antibiotics showed unsatisfactory result in this case. Computed tomography (CT) of the chest showed multiple pulmonary cavities with gas-fluid levels in the right upper and middle lobe, and patchy blurred shadows in the lower lobe. The diagnosis of fungal pneumonia was made after ruling out other causes of fever. The patient showed good response to anti-fungal treatment. Physicians must consider the possibility of fungal pneumonia in elderly patients who do not respond to antibiotic treatment after exclusion of immune response, tumor, tuberculosis, and other systemic infections.